The subjective experience of mind wandering in Alzheimer's disease. Issue 3 (3rd May 2020) - El Haj, Mohamad; Allain, Philippe; Antoine, Pascal; Gallouj, Karim; Moustafa, Ahmed A.; Quaglino, Véronique; Roche, Jean
ABSTRACT: Introduction: Little is known about mind wandering in Alzheimer's disease (AD). In this study, we evaluated the subjective experience of mind wandering in AD. Methods: We invited AD patients and control participants to rate the occurrence, intentionality, emotionality, visual imagery, specificity, self-relatedness and temporal orientation of mind wandering. Results: Analysis showed that AD patients rated their mind wandering as more frequent, negative, and more oriented toward the past, but less vivid and specific than that of control participants. No significant differences were observed between AD patients and control participants regarding the intentionality or self-relatedness of mind wandering. Conclusions: These findings demonstrate the negative content in AD. Regarding the reduction of visual imagery and specificity during mind wandering, this reduction may mirror a diminished subjective experience of mind wandering in AD. Regarding temporality, our results may reflect a tendency of AD patients to reminisce over past experiences. Finally, mind wandering in AD seems to trigger significant self-related content.